2021
DOI: 10.3168/jds.2021-20485
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum level of dietary cation-anion difference fed to nulliparous cows: Lactation and reproductive responses

Abstract: Supplemental Table 1. Characteristics of nulliparous cows enrolled in the experiment according to treatment Treatment 1 P-value 2 Item P200 N50 N150 SEM Linear Quadratic Cows 43 45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…One could postulate that some of the fatty acids detected in the calf's blood in the first hour of life might have originated from the dams through placental supply (Perazzolo et al, 2017). Acidogenic diets reduce DMI in prepartum cows (Zimpel et al, 2018), which was observed in the present experiment reported by Zimpel et al (2021a), and metabolic acidosis induced by acidogenic diets is known to reduce tissue insulin signaling in cows (Vieira-Neto et al, 2021). Perhaps the increased serum fatty acids in calves reflect increased maternal transfer of fatty acids.…”
Section: Discussionmentioning
confidence: 50%
“…One could postulate that some of the fatty acids detected in the calf's blood in the first hour of life might have originated from the dams through placental supply (Perazzolo et al, 2017). Acidogenic diets reduce DMI in prepartum cows (Zimpel et al, 2018), which was observed in the present experiment reported by Zimpel et al (2021a), and metabolic acidosis induced by acidogenic diets is known to reduce tissue insulin signaling in cows (Vieira-Neto et al, 2021). Perhaps the increased serum fatty acids in calves reflect increased maternal transfer of fatty acids.…”
Section: Discussionmentioning
confidence: 50%
“…In line with our findings, dietary zeolite supplementation during the last week of the pre-calving period significantly increased blood serum calcium concentration [ 2 , 14 ]. Conclusively, available reports have shown that feeding clinoptilolite or zeolite in the prepartum ration of dairy cows can reduce the frequency of hypocalcemia and prevent milk fever because zeolite can stabilize calcium in the intestinal tract and make it unabsorbable, which stimulates the physiological and hormonal mechanisms involved in increasing the level of blood Ca concentration [ 2 , 8 , 18 , 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important solution is restricted calcium availability, and the second solution is to make the cation-anion difference of the diet dietary cation–anion difference (DCAD) negative [ 5 7 ]. Decreasing the DCAD value to a level of—100 milliequivalents per kilogram (meq/kg) of dry matter (DM) induces mild acidosis and the release of parathyroid hormone at the time of delivery [ 8 , 9 ], which finally increases the amount of calcium absorption from the bones and will prevent milk fever and hypocalcemia [ 2 , 3 ]. To reduce the availability of dietary calcium, restricted rations during the transition period based on National Research Council (NRC) recommendations are used to control (CON) hypocalcemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors also identified the need to further understand the role of feeding acidogenic diets to nulliparous cows because of the scarcity and heterogeneity of the data currently available. Indeed, recent work showed limited benefits to feeding acidogenic diets to prepartum nulliparous cows [179,180]. Diet-induced metabolic acidosis is achieved by manipulating the mineral composition of the diet to result in a negative DCAD [181].…”
Section: Methods To Prevent Periparturient Mineral Imbalance 61 Alter...mentioning
confidence: 99%